2000
DOI: 10.1007/s002130000422
|View full text |Cite
|
Sign up to set email alerts
|

The effect of d -amphetamine on performance on two operant timing schedules

Abstract: These results confirm the disruptive effect of d-amphetamine on timing. The results of experiment 1 are consistent with the proposal that the drug reduces the period of the hypothetical pacemaker. However, the results of experiment 2 do not support this suggestion. Taken together, the results support the notion that different neural mechanisms may be involved in timing tasks involving temporal distribution of responding and discrimination of the duration of exteroceptive stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

26
63
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 63 publications
26
63
1
Order By: Relevance
“…There is increasing evidence from other procedures, however, that the neuropharmacological model does not account well for data from multiple experiments on the effects of dopamine agonists on timing (see also Chiang et al, 2000;Stanford & Santi, 1998). For example, although some studies using versions of the interval bisection task (Catania, 1970;Stubbs, 1968) have found effects of dopamine agonists that support the neuropharmacological model (e.g., Maricq & Church, 1983;Maricq et al, 1981;Meck, 1983;Spetch & Treit, 1984), other studies have not (e.g., Chiang et al, 2000;Lejeune et al, 1995;Odum & Schaal, 2000;Rapp & Robbins, 1976;Santi, Weise, & Kuiper, 1995;Stanford & Santi, 1998;Stubbs & Thomas, 1974).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing evidence from other procedures, however, that the neuropharmacological model does not account well for data from multiple experiments on the effects of dopamine agonists on timing (see also Chiang et al, 2000;Stanford & Santi, 1998). For example, although some studies using versions of the interval bisection task (Catania, 1970;Stubbs, 1968) have found effects of dopamine agonists that support the neuropharmacological model (e.g., Maricq & Church, 1983;Maricq et al, 1981;Meck, 1983;Spetch & Treit, 1984), other studies have not (e.g., Chiang et al, 2000;Lejeune et al, 1995;Odum & Schaal, 2000;Rapp & Robbins, 1976;Santi, Weise, & Kuiper, 1995;Stanford & Santi, 1998;Stubbs & Thomas, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…For example, although some studies using versions of the interval bisection task (Catania, 1970;Stubbs, 1968) have found effects of dopamine agonists that support the neuropharmacological model (e.g., Maricq & Church, 1983;Maricq et al, 1981;Meck, 1983;Spetch & Treit, 1984), other studies have not (e.g., Chiang et al, 2000;Lejeune et al, 1995;Odum & Schaal, 2000;Rapp & Robbins, 1976;Santi, Weise, & Kuiper, 1995;Stanford & Santi, 1998;Stubbs & Thomas, 1974). Studies with dopamine antagonists using the interval bisection task have found supporting evidence (Maricq & Church, 1983;Meck, 1983Meck, , 1986.…”
Section: Discussionmentioning
confidence: 99%
“…The psychophysical function describing the relation between the percentage of responses on the second operandum and the duration of the stimulus is taken as the measure of timing. Chiang et al (2000) found that with this procedure, d-amphetamine flattened the psychophysical function but did not shift it to the left. This result is interpreted as generalized disruption of timing without a particular distortion in perception (i.e., no overestimation or underestimation of time).…”
mentioning
confidence: 80%
“…There are a number of unresolved discrepancies in the literature on the effects of drugs on timing, however, which make general statements about the neuropharmacology of timing difficult (see e.g., Chiang et al, 2000;Odum, 2002;Odum, Lieving, & Schaal, 2002). For example, Chiang et al found that d-amphetamine had different effects on behavior maintained by different timing procedures.…”
mentioning
confidence: 99%
See 1 more Smart Citation